Inheritance and Innovation of Traditional Handicraft Skills based on Artificial Intelligence - Zhang, Yaping; He, Dongdong (Transactions on Computer Science and Intelligent Systems Research, 2023)
Today, with the strong return of traditional culture, the integration of the two will deeply affect the protection of traditional handicrafts and the field of cultural communication. The industrialized production mode has gradually replaced the labor-intensive production mode, and handicrafts have gradually faded out of the public consumption field. The brain drain is serious, and many handicrafts with a long history have no successors. Under the background of AI(artificial intelligence) empowerment, this paper combines AI with traditional handicraft skills, and makes an in-depth study on the inheritance and dissemination of traditional handicraft skills. On this basis, it further thinks about the relationship between traditional handicraft skills display and experience, and the relationship between technology and experience, and studies the change of design concept from technology-oriented to human experience-oriented in traditional handicraft skills display design, and explores the development trend of experience design concept in future traditional handicraft skills display design. Develop the path and method of innovation, protection and inheritance with the comprehensive digital virtual traditional handicraft skill framework. The integration of AI and traditional culture will inevitably broaden and upgrade the path of inheritance and innovation of traditional handicraft skills, and make it achieve new development.